2022
DOI: 10.1186/s12915-022-01311-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species discrimination of vocal expression of emotional valence by Equidae and Suidae

Abstract: Background Discrimination and perception of emotion expression regulate interactions between conspecifics and can lead to emotional contagion (state matching between producer and receiver) or to more complex forms of empathy (e.g., sympathetic concern). Empathy processes are enhanced by familiarity and physical similarity between partners. Since heterospecifics can also be familiar with each other to some extent, discrimination/perception of emotions and, as a result, emotional contagion could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…An additional issue is whether heterospecific emotion perception is best explained by evolutionary homology, familiarity, or domestication ( Maigrot, Hillmann & Briefer, 2022 ). Most previous studies of human perception have used sounds from domestic animals such as cats, dogs, and livestock (for exceptions, see Filippi et al (2017a) , Kelly et al (2017) , Fritz et al (2018) and Kamiloǧlu et al (2020) ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional issue is whether heterospecific emotion perception is best explained by evolutionary homology, familiarity, or domestication ( Maigrot, Hillmann & Briefer, 2022 ). Most previous studies of human perception have used sounds from domestic animals such as cats, dogs, and livestock (for exceptions, see Filippi et al (2017a) , Kelly et al (2017) , Fritz et al (2018) and Kamiloǧlu et al (2020) ).…”
Section: Introductionmentioning
confidence: 99%
“…These, of course, are species with which many humans are familiar—and indeed, which might have undergone evolutionary changes in emotional expression to improve communication with humans ( Pongrácz, Molnár & Miklósi, 2010 ). Some studies have suggested accurate perception does not depend on familiarity ( Pongrácz et al, 2005 ; Filippi et al, 2017a ; Merkies, Crouchman & Belliveau, 2021 ; Maigrot, Hillmann & Briefer, 2022 ), but several have demonstrated an association between experience with a particular species and increased accuracy in recognizing the emotional significance of its vocalizations ( Nicastro & Owren, 2003 ; McComb et al, 2009 ; Tallet et al, 2010 ; Scheumann et al, 2014 ; Faragó et al, 2017 ; Parsons et al, 2019 ). This raises the question of the degree to which human accuracy in heterospecific emotion recognition tasks reflects evolutionary homology, as opposed to a capacity to learn to recognize any individual species’ unique emotional expressions through exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Through multiple generations of this interdependent relationship, goats and other domesticated species have undoubtedly become well-adapted to occupying this anthropogenic niche, perhaps predisposing them towards more advanced social cognition of our cues (Hare et al, 2005), including emotional ones. This appears to be the case in pigs, with domestic pigs but not wild boar (Sus scrofa) behaving differently to human voices based on the valence they express (Maigrot et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, some livestock have been shown to read a variety of human cues sometimes showing comparable levels of performance to companion animals. For example, pigs (Sus scrofa domesticus) respond differently to human voices based on their emotional valence (Maigrot et al, 2022) and cows (Bos taurus) can discriminate chemical cues, preferring to interact with sweat odours collected from humans in neutral, but not in stressful situations (Destrez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, research on whether domestic animals interpret distress and alarm calls as such and react to them accordingly is still limited and may present some contradictions. For example, previous work on pigs revealed that individuals showed similar behavioral and physiological reactions following the playbacks of both conspecific distress calls and a neutral control sound [30], while recent research revealed a contrary pattern: pigs do discriminate negative and positive conspecific vocalizations (vocalizations made during social isolation and when in pairs, with access to food, water, and toys, respectively) [32].…”
Section: Introductionmentioning
confidence: 99%